Understanding the Concept of Ghuluw in the Qur’an: An Analysis of Al-Maraghi’s Tafsir and Its Relevance to Modern Religious Practices: (Memahami Konsep Ghuluw dalam Al-Qur’an: Analisis atas Tafsir Al-Maraghi dan Relevansinya Terhadap Praktik Keagamaan Kontemporer) - Muhammad Nizamuddin; Muhamad Amrulloh; Murdianto Murdianto (Al Muhafidz: Jurnal Ilmu Al-Qur'an dan Tafsir, 2026)
Religious extremism (ghuluw) represents a critical theological and social challenge requiring contextual interpretation of Qur'anic texts. This research investigates the conceptualization of ghuluw through comparative exegetical analysis, examining interpretations from classical scholars (Al-Ṭabari, Al-Razi) and contemporary commentators (Al-Maraghi, Quraish Shihab, Hamka, Ṭabaṭaba'i) regarding QS. Al-Nisa' [4]:171 and QS. Al-Ma'idah [5]:77. Employing library research methodology with thematic (mawdu'i) and comparative approaches, this study positions Al-Maraghi's Tafsir as the primary analytical framework, complemented by systematic cross-referencing of six major exegetical works spanning classical and modern periods. The research identifies three principal findings: 1) ghuluw emerges from the interplay of theological misconceptions, unchecked desires (hawa nafsu), and rational deficit in religious understanding; 2) classical and contemporary exegetes demonstrate convergent emphasis on wasaṭiyyah (moderation) as the foundational antithesis to extremist tendencies; 3) Al-Maraghi's adabi ijtima'i (socio-literary) methodology provides actionable frameworks for addressing contemporary polarization phenomena in Indonesian Muslim communities. Empirical contextualization through documented cases—including the Sampang sectarian conflict (2012) and intolerance survey data—illustrates the persistent relevance of Qur'anic prohibitions against religious excess. This investigation transcends normative-theological discourse by integrating textual exegesis with socio-political analysis, thereby contributing a dual-function scholarship: deepening theoretical understanding of ghuluw while simultaneously offering practical deradicalization strategies rooted in Islamic moderation principles. The study's significance lies in bridging the gap between classical hermeneutics and contemporary challenges of religious extremism, radicalism, and sectarian fragmentation within Indonesia's pluralistic context.